Racial/ethnic disparities in severe maternal morbidity: An intersectional lifecourse approach. Issue 1 (27th September 2022) - Hailu, Elleni M.; Carmichael, Suzan L.; Berkowitz, Rachel L.; Snowden, Jonathan M.; Lyndon, Audrey; Main, Elliott; Mujahid, Mahasin S.
Abstract: Despite long‐existing calls to address alarming racial/ethnic gaps in severe maternal morbidity (SMM), research that considers the impact of intersecting social inequities on SMM risk remains scarce. Invoking intersectionality theory, we sought to assess SMM risk at the nexus of racial/ethnic marginalization, weathering, and neighborhood/individual socioeconomic disadvantage. We used birth hospitalization records from California across 20 years (1997–2017, N = 9, 806, 406) on all live births ≥20 weeks gestation. We estimated adjusted average predicted probabilities of SMM at the combination of levels of race/ethnicity, age, and neighborhood deprivation or individual socioeconomic status (SES). The highest risk of SMM was observed among Black birthing people aged ≥35 years who either resided in the most deprived neighborhoods or had the lowest SES. Black birthing people conceptualized to be better off due to their social standing (aged 20–34 years and living in the least deprived neighborhoods or college graduates) had comparable and at times worse risk than White birthing people conceptualized to be worse off (aged ≥35 years and living in the most deprived neighborhoods or had a high‐school degree or less). Our findings highlight the need to explicitly address structural racism as the driver of racial/ethnic health inequities and the imperative to incorporate intersectional approaches. Abstract : Despite long‐existing calls to address alarming racial/ethnic gaps in severe maternal morbidity (SMM), research that considers the impact of intersecting social inequities on SMM risk remains scarce. Invoking intersectionality theory, we sought to assess SMM risk at the nexus of racial/ethnic marginalization, weathering, and neighborhood/individual socioeconomic disadvantage.